Implementation of Cash Waqf Management (Studies at the Ziswaf Board of Kopontren Al Yasini Pasuruan) - Muhammad Rif'an Syadali; Nur Asnawi; Parmujianto Parmujianto (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
Waqf is one of the instruments of the Islamic economy that aims to achieve the objectives of the Islamic economy, namely producing a rich life. The concept of Waqf is still considered to be the practice of the rich, because the payment is identical to that of land and buildings. Currently, in Indonesia, there is a new method of paying off the waqf that is available, this is cash-based and is derived from Law number 41 of 2004 regarding the management of cash-based funds associated with the waqf. This investigation describes the procedure of implementing cash waqf in the Al-Yasini Kopontren Ziswaf Agency as an Amil Zakat Organization that has employed cash waqf. This research employs a qualitative methodology with data analysis methods that involve interaction. From the research results, it is apparent that the utilization of cash funds at the Al-Yasini Kopontren Ziswaf Board is invested in the form of shares in the retail business "Al Yasini Mart". The income from the dividend is dedicated to funding scholarships for impoverished, unfortunate, and unlucky Al-Yasini Islamic Boarding School students, students who are exceptional in school, and hafidz students who memorize the Quran.